Testing the Purity of Limnospira fusiformis Cultures After Axenicity Treatments - Michael Schagerl; Alexander Kaptejna; Fabian Polz; Sameh S. Ali; Shuhao Huo; Joana Seneca; Petra Pjevac; Vera Hechtl (Cells)
Contaminations are challenging for monocultures, as they impact the culture conditions and thus influence the growth of the target organism and the overall biomass composition. In phycology, axenic cultures comprising a single living species are commonly strived for both basic research and industrial applications, because contaminants reduce significance for analytic purposes and interfere with the safety and quality of commercial products. We aimed to establish axenic cultures of Limnospira fusiformis, known as the food additive “Spirulina”. Axenicity is strived because it ensures that pathogens or harmful microorganisms are absent and that the harvested biomass is consistent in terms of quality and composition. For the axenic treatment, we applied sterile filtration, ultrasonication, pH treatment, repeated centrifugation, and administration of antibiotics. For testing axenicity, we considered the most common verification method plate tests with Lysogeny Broth (LB) medium, which indicated axenicity after treatments were performed. In addition, we included plate tests with Reasoner’s 2A (R2A) agar and modified Zarrouk+ medium, the latter comparable to the biochemical properties of L. fusiformis’ cultivation medium. In contrast to LB plates, the other media, particularly Zarrouk+, indicated bacterial contamination. We conclude that LB-agar plates are inappropriate for contamination screening of extremophiles. Contamination was also verified by cultivation-independent methods like flow cytometry and 16S rRNA genome amplicon sequencing. We detected taxa of the phyla Proteobacteria, Bacteriodota, Firmicutes and to a lesser extent Verrucomicrobiota. Contaminants are robust taxa, as they survived aggressive treatments. Sequencing data suggest that some of them are promising candidates for in-depth studies to commercially exploit them.